Pengaruh Iklan Shopee di YouTube terhadap Minat Beli - Febriana, Alda; Najmuddin, Abdul Latif; Supriatno, Djoko (Program Studi Ilmu Komunikasi, 2024)
Indonesians shopping habits change over time. Indonesian shopping has many trends, from late-night shopping to online shopping which is currently on the rise. The shift to online shopping facilitated by various online platforms has fueled competition among these online stores. Shopee one of the online marketplaces, joined the market as a result of the e-commerce boom in Indonesia. Referring to the background previously described, the problem formulation is: How is the Effect of Shopee Ads on YouTube on Buying Interest? Advertising Exposure Theory by Aaker, Batra & Myers. This theory provides an explanation of what happens to customers after they are exposed to advertisements. This research uses a quantitative approach with the type of survey research. The population of this study were residents of Rt 003 / Rw 003 Sumber Jeruk Village, Kalisat District, Jember Regency. The sampling technique used purposive sampling with a total sample size of 54 respondents. The results of this study indicate that there is an effect of Shopee Ads on YouTube on Purchase Interest, as evidenced by the regression result of 0.397 with a t value of 5.037> t table 2.007 this value shows that H0 is rejected Ha is accepted, which means that there is an effect of Shopee Ads on YouTube on Purchase Interest.